Pertumbuhan dan Regenerasi Alami Shorea platyclados di Hutan Penelitian Gunung Dahu, Leuwiliang, Bogor: Growth and Natural Regeneration of Shorea platyclados in Gunung Dahu Research Forest, Leuwiliang, Bogor - Fatimah Azzahra; Prijanto Pamoengkas (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Indonesia has the third largest tropical rainforest in the world, dominated by Dipterocarpaceae family, including meranti (Shorea spp.), which has high economic value. Shorea platyclados plays an important role in the revegetation of logged-over forests in Indonesia, making it essential for forest rehabilitation and production forest management. This study aimed to analyze the growth performance and natural regeneration potential of S. platyclados in Gunung Dahu Research Forest. The study was conducted in four blocks (Blocks 4, 15, 20, and 21e), observing diameter at breast height (DBH), total tree height, number of individuals, slope, elevation, and canopy cover. The results showed that the average diameter ranged from 39,40–45,16 cm (MAI 1,52–1,74 cm year⁻¹), and the average stand height ranged from 18,49–22,34 m (MAI 0,68–0,86 m year⁻¹). Overall, both diameter and height growth were classified as very fast. Slope significantly affected diameter but had no significant effect on height, whereas canopy cover had a highly significant effect on both diameter and height. The natural regeneration potential of S. platyclados was categorized as good, indicated by 206 seedlings with an average density of 123.214 individuals ha⁻¹.